Factors influencing the length of stay among patients admitted to a tertiary pediatric intensive care unit in Saudi Arabia - Alshaikh, Reem; AlKhalifah, Ahmed; Fayed, Amel; AlYousef, Sawsan (Frontiers in Pediatrics, 2022)
This study aimed to assess the variables contributing to the length of stay in the pediatric intensive care unit. This study utilized a retrospective design by analyzing data from the Virtual Pediatric Systems web-based database. The study was conducted in a tertiary hospital—King Fahad Medical City in Riyadh, Saudi Arabia—from January 1, 2014 to December 31, 2019. The patients were admitted to intensive care with complex medical and surgical diseases. The variables were divided into quantitative and qualitative parameters, including patient data, Pediatric Risk of Mortality III score, and complications. Data from 3,396 admissions were analyzed. In this cohort, the median and mean length of stay were 2.8 (interquartile range, 1.08-7.04) and 7.43 (standard deviation, 14.34) days, respectively. The majority of long-stay patients—defined as those staying longer than 30 days—were less than 12 months of age (44.79%), had lower growth parameters (p < 0.001), and had a history of admission to pediatric intensive care units. Moreover, the majority of long-stay patients primarily suffered from respiratory diseases (51.53%) and had comorbidities and complications during their stay (p < 0.001). Multivariate analysis of all variables revealed that central line-associated bloodstream infections (p < 0.001), external ventricular drain insertion (p < 0.005), tracheostomy (p < 0.001), and use of mechanical ventilation (p < 0.001) had the most significant associations with a longer stay in the pediatric intensive care unit. The factors associated with longer stays included the admission source, central nervous system disease comorbidity, and procedures performed during the stay. Factors such as respiratory support were also associated with prolonged intensive care unit stays.